2010
DOI: 10.1167/iovs.09-3587
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Refractive Error in Singaporean Chinese Children: The Strabismus, Amblyopia, and Refractive Error in Young Singaporean Children (STARS) Study

Abstract: The prevalences of myopia and astigmatism in young Singaporean Chinese children are high, but that of hyperopia is low. Age effects were observed for each refractive error category, but differences between the sexes were not significant. Age-related variation in myopia prevalence may be influenced by ocular development, environment, and/or testability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
161
8
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 195 publications
(197 citation statements)
references
References 33 publications
26
161
8
2
Order By: Relevance
“…Prevalence of myopia in young Chinese children has been noted to be generally higher-ranging from 5.5 to 38.1% in children aged 6 months to 15 years of age [3][4][5] -compared with that found by studies in the West where prevalence rates ranged from 0.8 to 11.9% in predominantly young Caucasian children aged 6 months to 12 years of age. [6][7][8] Several environmental risk factors have been implicated in development of myopia including family history 9 and near work, 10 while breastfeeding has been identified as a possible protective factor.…”
Section: Introductionmentioning
confidence: 72%
“…Prevalence of myopia in young Chinese children has been noted to be generally higher-ranging from 5.5 to 38.1% in children aged 6 months to 15 years of age [3][4][5] -compared with that found by studies in the West where prevalence rates ranged from 0.8 to 11.9% in predominantly young Caucasian children aged 6 months to 12 years of age. [6][7][8] Several environmental risk factors have been implicated in development of myopia including family history 9 and near work, 10 while breastfeeding has been identified as a possible protective factor.…”
Section: Introductionmentioning
confidence: 72%
“…30 In Singapore, the prevalence of myopia was 29.0% in 7-year-olds, 34.7% in 8-year-olds and 53.1% in 9-year-olds in the school-based population of the Singapore Cohort Study of Risk factors for Myopia (SCORM) 36 while the Strabismus, Amblyopia and Refractive error Study in Singapore Preschool Children (STARS) reported that the prevalence of myopia was 11.0% in Chinese children aged 6-72 months. 37 In Hong Kong, a large cross-sectional survey reported that the prevalence was 17.0% in children aged <7 years and which increased to 37.5% among those aged 8 years and 53.1% in children aged more than 11 years. 38 The prevalence of myopia among Taiwanese Chinese primary school children aged 7 years was 5.8% in 1983, 3.0% in 1986, 6.6% in 1990, 12.0% in 1995 and 20.0% in 2000.…”
Section: Prevalence Of Myopia In Adults In Western Countriesmentioning
confidence: 99%
“…Myopia is a public health problem in East Asia, with prevalence rates in Singapore of 8% in 5-year olds 1 and 36.3% in 7-9-year-old school children, 2 and nearly 40% in adults Z40 years. 3 Although there have been many studies that have documented the risk factors for myopia, there is no conclusive evidence that modifying these risk factors may have an impact on the prevalence of myopia.…”
Section: Introductionmentioning
confidence: 99%